The Burman his life and notions - Scott, James George 1851-1935 (Norton, 1963)
"Only one Western writer has ever been able to capture fully the spirit of the delightful inhabitants of Burma. Whether describing the childbirth rites, the function of the astrologers in Burmese society, or the Buddhist precepts by which the good Burman lives, "Shway Yoe"--The pseudonym of Sir J. George Scott, K.C.I.E., a British civil servant who spent more than thirty years in Burma -- fills his books with a broad sympathy for the Burmese society he knew."--Cover.
Keywords: Geschichte 1882; Alltag, Brauchtum; Kultur; Birmanie - Moeurs et coutumes; Burma -- Social life and customs; Birma; Erlebnisbericht